A further view on current account, capital account and Target2 balances: Assessing the effect on capital structure and economic welfare - Friedrich L. Sell; Beate Sauer (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2011)
In this paper, we first present the state and the development of the European capital and current account imbalances. We demonstrate how large the heterogeneity among European countries is and that clustering here different types of countries is possible, but that it leads to different groupings than what has been labeled the PIGS or better GIPS countries on the one side and the GLNF countries on the other side. The same applies when it comes to cluster countries according to the debt ratio criterion. Hereafter, we put forward our own description of the mentioned ECB implicit financing scheme(s), among other things extending and complementing the recent base money market (supply and demand) analysis given by H.-W. Sinn and T. Wollmershäuser (2011). The core of the paper consists in a modified model of the New Austrian School of Economics - in the tradition of F. A. v. Hayek (1929, 1931) and in the vein of R. M. Garrison (2002) - which enables us to discuss the current distortions introduced by the Target2 credit channel into the capital markets of selected EMU countries and to detect its most important economic consequences. This part of the paper ends with a static welfare evaluation. Finally, we come up with some conclusions and suggestions for economic policy.
Keywords: D61; E52; E58; F32; F34; 330; Target2 balances; current account deficits; ECB monetary policy; New Austrian Economics